If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-4)=7F+3
We move all terms to the left:
(-4)-(7F+3)=0
We add all the numbers together, and all the variables
-(7F+3)-4=0
We get rid of parentheses
-7F-3-4=0
We add all the numbers together, and all the variables
-7F-7=0
We move all terms containing F to the left, all other terms to the right
-7F=7
F=7/-7
F=-1
| 6y^×=y+1 | | 4x3^7x=9x2^7x | | 4x3^7x=9x2^7x | | 4x3^7x=9x2^7x | | 2.77+x+3.00=3.00 | | 8(x+1)=29 | | 8(x+1)=29 | | 8(x+1)=29 | | 8(x+1)=29 | | 8(x+1)=29 | | 8(x+1)=29 | | 8(x+1)=29 | | 8(x+1)=29 | | 8(x+1)=29 | | 8(x+1)=29 | | 60°+53°+x=180 | | 60°+53°+x=180 | | 60°+53°+x=180 | | 2.77+x+3.00=3.00 | | 60°+53°+x=180 | | 8(x+1)=29 | | 60°+53°+x=180 | | 8(x+1)=29 | | 8(x+1)=29 | | 60°+53°+x=180 | | 8(x+1)=29 | | 6w=30- | | 6000.00=3000.00(1+(5r) | | 6000.00=3000.00(1+(5)r) | | x/18-4/5=0 | | x/18-4/5=0 | | 8x-5=10-4(-2x+3) |